SHOULD antéposé dans les propositions hypothétiques - Valérie Bourdier (Anglophonia)
This article is a study of the use of the modal auxiliary SHOULD in hypothetical constructions exhibiting subject-auxiliary inversion. The examination of authentic examples taken from a variety of sources suggests that hypothetical “should-clauses” anaphorize covert preconstructed predicative relations so that the possible compatibility of qualities between the relation and the notional frame of reference is called into question. It is thus argued that such clauses develop the qualitative dimension of the anaphorized predicative relation by re-situating it relative to both existential and evaluative intersubjective alternative values.